Studie logistické koncepce pro obchodní síť - Jankůj, Robert (Vysoké učení technické v Brně. Fakulta podnikatelská, 2008)
Tato diplomová práce je návrhem logistické koncepce a realizace vývozu propagačních a reklamních předmětů na trhy východní Evropy a střední Asie.

The master’s thesis devises a logistical concept as well as the execution of promotional and advertising commodities’ exportation to the markets of Eastern Europe and Central Asia.
The Study of Logistic Conception for Trading Network
Keywords: Mezinárodní obchod; logistika; INCOTERMS 2000; clo.; International trade; logistics; INCOTERMS 2000; customs duty.